Происхождение этнического названия бурят - Б. Р. Зориктуев, (Acta Mongolica, 2015)
The problem of the origination of the name buryat is one of the ancient in the buryat study. The results of the latest research was obtained by identifying and studying a large number of new sources and the revision of the existing approaches to the disclosure of the etymology of the ethnonims.